Harmful Effects of Nanoparticles on Animals - Jean-Marie Exbrayat; Elara N. Moudilou; Emmanuel Lapied (Journal of Nanotechnology)
Since several years nanoparticles (NPs) are produced by industries and used in several fields of activities. They are finally found in aquatic and terrestrial environments, where they are ingested by living organisms in which they accumulate, before being eliminated. In organisms, NPs represent foreign elements with their own physicochemical properties due to their small size. So NPs may interfere with the normal physiological mechanisms of the embryos, growing animals, and adults, and it is indispensable to understand their potentially direct or indirect harmful effects on living organisms. It has been already shown that NPs could be toxic to bacteria, algae, invertebrates, and vertebrates. In this review, several examples of recent studies are given. We will examine successively the effects of NPs on terrestrial and semiaquatic and aquatic vertebrate and invertebrate animals.